Interview with Gabriel Villalón, Epistemological Journey of a Researcher in Teaching of Social Sciences - Ubilla Sánchez, Gerardo (2022)
In this interview, Gabriel Villalón Gálvez, Chilean researcher, let us know his journey in the field of teaching in social sciences. During the talk, we visit the first decisions that got him to opt for the research about History teaching, and his reflections related with the didactical content knowledge and its development in preservice and in-service teachers. In the last stage of this dialog, he refers to the personal and professional relationship with Joan Pagès Blanch (1947-2020), his doctoral thesis advisor, and he shares with us his current questions concerning the tie between the History teaching in schools, and the building of citizenships.